2015
DOI: 10.3892/mmr.2015.4093
|View full text |Cite
|
Sign up to set email alerts
|

Cross-reactivity between group-5 and -21 mite allergens from Dermatophagoides farinae, Tyrophagus putrescentiae and Blomia tropicalis

Abstract: Abstract. Group-5 and group-21 allergens, produced by house dust mites and storage mites are 36.6-55.8% identical in their sequences and are recognized by at least 50% of immunoglobulin (Ig)E from the sera of individuals allergic to dust mites. In the present study, recombinant group-5 and -21 allergens from three mite species, Dermatophagoides farinae (rDer f 5 and 21), Tyrophagus putrescentiae (rTyr p 5 and 21), and Blomia tropicalis (rBlo t 5 and 21), were purified from Escherichia coli, and the IgE reactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 25 publications
0
18
1
1
Order By: Relevance
“…In contrast, most studies have focused on cross-reactivity between B. tropicalis and other mites [33,53,101,107]. At least 5 cross-reactive allergens have been identified in extracts of Euroglyphus maynei and B. tropicalis [108].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, most studies have focused on cross-reactivity between B. tropicalis and other mites [33,53,101,107]. At least 5 cross-reactive allergens have been identified in extracts of Euroglyphus maynei and B. tropicalis [108].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the low sequence identity scores, some degree of cross-reactivity between group 5 and 21 allergens of B. tropicalis and Dermatophagoides has been reported; however, while Der f 5 could inhibit 60% of IgE binding to Blo t 5, there was no inhibition in the opposite direction [53]. Similarly, the cross-reactivity between Der p 1 and Blo t 1 was shown to be moderate [32], as was that between Blo t 5 and Der p 5 [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 En los países del trópico, los ácaros son la principal causa de atopia; 9,10 los mayormente reportados son Dermatophagoides pteronyssinus, Dermatophagoides farinae y Blomia tropicalis. 11,12,13,14 Los estudios epidemiológicos han mostrado que no todas las poblaciones están expuestas a los diferentes ácaros en la misma proporción, 6,7 sin embargo, debido a la reactividad cruzada entre algunas proteínas, las personas que tienen una sensibilización IgE a proteínas que se mantienen conservadas entre diferentes especies, pueden presentar síntomas con fuentes a las que no están expuestos si estas presentan estas proteínas. 15 Usualmente esto ocurre entre proteínas fi logenéticamente conservadas con alta identidad que reciben el nombre de "panalérgenos" y están presentes en fuentes ancestralmente relacionadas.…”
Section: Antecedentesunclassified
“…Studies have shown that more than 80% of BT sensitized patients react to Blo t 5 and Blo t 21 [23]. Blo t 5 and Blo t 21 share a moderate degree of homology, but the IgE cross-reactivity between the 2 allergens is very limited [24-26]. Thus, Blo t 5 or Blo t 21 are defined as BTMA [27, 28].…”
Section: Introductionmentioning
confidence: 99%